SLOPE STABILITY TECHNICAL STUDY USING SLOPE MASS RATING (SMR) METHOD AT PT. KARYA SUMBER ALAM PERKASA, SANGGAU REGENCY, KALIMANTAN BARAT - Wildani, Elgi; Meilasari, Fitriana; Purwoko, Budhi; Sutrisno, Hendri; Syahrudin, Syahrudin (Jurnal Teknik Sipil, 2022)
Soil (topsoil and overburden) above the granite quarry in pit 2 (two) PT. Karya Sumber Alam Perkasa has experienced a landslide. It is probably caused by the condition of pit 2 (two) slopes at PT. Karya Sumber Alam Perkasa, which is currently being mined, is quite steep. External factors that can trigger the movement of rock masses are vibrations due to breakers. This condition has the potential to increase the risk of slope stability. Slope stability is influenced by geological conditions, joints, slope geometry, water conditions below the soil surface, physical and mechanical properties, and vibrations due to blasting and mechanical equipment. Therefore, it is necessary to conduct a technical study of slope stability. The research aims to study rock mass class, potential type of landslide, and potential slope stability. The technical study of slope stability uses the Slope Mass Rating (SMR) method. Data processing using software Rocscience Dips 7.016. Analysis of potential types of landslides based on stereographic projections. The result of the RMR calculation is 78, so the rock mass class is number II, which is included in the excellent category. The results analysis of the potential for the type of failure indicates t tends to lead to the toppling failure, but after the study, there is no failure because it does not meet the landslide requirements. The result of the analysis of potential slope stability is that the slope in pit 2 (two) is safe or stable because the SMR value is 78 and the safety factor value is 2,458.